HUBUNGAN KUALITAS KOMUNIKASI TIM MEDIS DENGAN HASIL PERAWATAN PASIEN IGD DI RUMAH SAKIT ISLAM SULTAN HADLIRIN JEPARA - Dwi Widodo; Ratna Ratna; Feri Catur Yuliani (CV. KAMPUS AKADEMIK PUBLISHING, 2025)
Abstract In the modern era, the quality of health services is a major focus in improving public health. A preliminary study at the Emergency Room of Sultan Hadlirin Islamic Hospital, Jepara, on May 14, 2025, showed that there were still communication obstacles between teams, such as delays in delivering information between shifts and nurses' lack of understanding of doctor's instructions. From interviews with five nurses and two doctors, obstacles were found in work coordination, while out of 10 patients or patient families, four people stated that they were dissatisfied with the speed and clarity of medical explanations. The purpose of the study was to determine the relationship between the quality of medical team communication and patient care outcomes in the Emergency Room of Sultan Hadlirin Islamic Hospital, Jepara. The type of research was quantitative with a correlation method and a cross-sectional design. The research sample was 43 respondents. The results of statistical tests with the Chi Square test obtained a p-value of 0.002 (p <0.05). The conclusion is that there is a relationship between the quality of medical team communication and patient care outcomes in the Emergency Room of Sultan Hadlirin Islamic Hospital, Jepara. Keywords: communication, medical, emergency room Abstrak. Dalam era modern, kualitas pelayanan kesehatan menjadi fokus utama dalam meningkatkan derajat kesehatan masyarakat. Studi pendahuluan di Instalasi Gawat Darurat RSI Sultan Hadlirin Jepara pada 14 Mei 2025 menunjukkan masih adanya kendala komunikasi antartim, seperti keterlambatan penyampaian informasi antarshift dan kurangnya pemahaman perawat terhadap instruksi dokter. Dari wawancara dengan lima perawat dan dua dokter, ditemukan hambatan dalam koordinasi kerja, sedangkan dari 10 pasien atau keluarga pasien, empat orang menyatakan kurang puas terhadap kecepatan serta kejelasan penjelasan medis.Tujuan penelitian mengetahui hubungan kualitas komunikasi tim medis dengan hasil perawatan pasien di IGD RSI Sultan Hadlirin Jepara. Jenis penelitian adalah kuantitatif dengan metode korelasi dan desain cross sectional. Sampel penelitian sebanyak 43 responden.Hasil uji statistik dengan uji Chi Square didapatkan nilai p p-value 0.002 (p< 0.05).Kesimpulan terdapat Hubungan Kualitas Komunikasi Tim Medis Dengan Hasil Perawatan Pasien di IGD RSI Sultan Hadlirin Jepara Kata Kunci: komunikasi,medis,IGD